2022
DOI: 10.1007/s11694-022-01289-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of Egyptian grape and mulberry by-products and their potential use as natural sources of food additives and nutraceuticals foods

Abstract: Interest in the biological role of bioactive compounds present in plant by-products has increased over the last few years. This study aimed to investigate the nutritive value and biological activities of Egyptian Grape leaves (GL), Grape seeds (GS) and Mulberry leaves (ML), as well as investigate the impact of γ-irradiation for improving the utilization of these plant byproducts. The dose level 5.0 kGy showed highest the content of crude protein (24.42, 19.41 and 13.50 mg/100 g), as well as crude fiber (34.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
(71 reference statements)
2
3
0
Order By: Relevance
“…Among individual phenolic content, the amounts of gallic and protocatechuic were higher than other phenolic acids. These findings were consistent with those of Abdel-Khalek and Mattar [8] who discovered the presence of phenolic compounds in Egyptian grape leaves, grape seeds, and mulberry leaves. They discovered that phenolic compounds differed in the methanolic extracts of all samples.…”
Section: Phenolic Acids Identification and Antioxidants Capacity In A...supporting
confidence: 92%
See 3 more Smart Citations
“…Among individual phenolic content, the amounts of gallic and protocatechuic were higher than other phenolic acids. These findings were consistent with those of Abdel-Khalek and Mattar [8] who discovered the presence of phenolic compounds in Egyptian grape leaves, grape seeds, and mulberry leaves. They discovered that phenolic compounds differed in the methanolic extracts of all samples.…”
Section: Phenolic Acids Identification and Antioxidants Capacity In A...supporting
confidence: 92%
“…These results are in accordance with Meral and Do gan [68]. Catechin and epicatechin are phenolic compounds found in GSP [8]. These compounds have an impact on the color of products.…”
Section: Sensory Properties Of Balady Bread Supplemented With Differe...supporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies using pomegranate, purple cauliflower, and purple cabbage have shown that flavonoids have a strong ability to scavenge free radicals [30]. In recent years, functional foods rich in flavonoids have received much attention for their beneficial effects [32]. One study found that phenolic compounds extracted from blackberries are growth-inhibiting compounds with anticancer activity [33].…”
Section: Discussionmentioning
confidence: 99%